Blood on the river : James Town 1607 - Carbone, Elisa (New York : Viking, 2006)
Traveling to the New World in 1606 as the page to Captain John Smith, twelve-year-old orphan Samuel Collier settles in the new colony of James Town, where he must quickly learn to distinguish between friend and foe.
Includes bibliographical references.
A Junior Library Guild selection.
Keywords: Powhatan Indians. -- Fiction; Indians of North America. -- Virginia -- Fiction; Powhatan Indians. -- Fiction; Indians of North America. -- Virginia -- Fiction